Response of broiler chickens to dietary supplementation of L-glutamine and L-glutamate under stressful conditions - Shakeri, Majid (2014)
High stocking density (HSD) and delay in placement are practices that may impair growth performance and well-being of broiler chickens. Dietary supplementation with L- glutamine and L-glutamate (LG) has been suggested to improve poultry performance under stressful conditions. Thus, this research was conducted to evaluate the effect of LG supplementation on performance, gut morphology, physiology and well-being of broiler chickens subjected to different stocking densities and posthatch holding times. In Chapter 3, one-day-old broiler chicks were stocked either at 10 birds/m 2 or 15 birds/m 2 and assigned to four dietary treatments namely (i) basal diet (ii) basal diet supplemented with 0.5% LG from 1 -21 days of age (LG3), (iii) basal diet supplemented with 0.5% LG for from 1 - 42 days of age (LG6), (iv) and basal diet supplemented with virginiamycin from 1 - 42 days of age (VM). The results indicated that neither LG3 nor LG6 had beneficial effects on growth performance, duodenal villi and crypt depth, gut E. coli and Lactobacilli counts, and incidence of food pad dermatitis. VM improved growth performance, villi length and decreased the population of E. coli. Irrespective of LG and VM supplementation, the high stocking density impaired growth performance, and villi length, and increased incidence of foot pad dermatitis. The high stocking density elevated serum levels of ceruloplasmin (CP) , ul acid glycoprotein (AGP), corticosterone (CaRT), and heterophil/lymphocyte ratios (HLR) as compared to the low stocking density. In Chapter4, broiler chicks were subjected to either immediate placement or delayed placement (24 hours after arrival). Chicks from each placement time were supplemented with LG at 1% from 1 -21 day of age or unsupplemented diet. Chicks subjected to 24 hours of delayed placement had larger yolk sac, and poorer early weight gain (during 1 -21 days of age) than their control counterparts. However, the final weight gain and feed conversion ratios (FCR) of the chicks subjected to immediate and delayed placement were not significantly different. Delayed placement had no significant effect on gut morphology, CP, AGP, QVT, and duodenal heat shock protein (HSP) 70 density at 21 days of age. Supplementing birds with LG increased duodenal villi length and crypt depth at 21 days of age, and improved final weight gain, FCR and survivability when compared to controls. The CP, AGP, OVT and HSP 70 density of chicks subjected to delayed placement were elevated when compared to controls. The present findings suggested that LG supplementation at 1% from day 1 - 21 days of age can improve weight gain, FCR, and gut morphology of chicks subjected to 24 hours of delayed placement. Supplementing chicks with LG may also aid chickens to cope with stresses through elevation in APP and HSP 70.